Human connection and social development : lessons learned from a summer in Ghana - White, Erin (My University, 2015)
I had the opportunity to spend the majority of the summer of 2010 interning in Ghana with an organization called Disaster Volunteers of Ghana. I lived with a host famly in a village called Sogakope. I was one of three white people in the entire village, the other two being the friends I went with. I spent my days teaching at the local school that also housed the orphanage; depending on the needs of the day I taught anything from kindergarten to junior high. After the school day ended, I played with the kids and helped them with chores and homework. I spent every afternoon entertaining the children without television, video games, bikes, fancy sports equipment or computers. It was quite the challenge. Before my internship in Ghana, I idealized the concept of service. When my plans to work in an orphanage with children all summer were cemented, visions of smiling, laughing, joyful and adorable children danced in my head: inspiring all fundraising and preparation efforts, leading to the negation of any realistic mental preparation for the challenges and hardships that were sure to be faced. Living and working in Ghana for seven weeks was an extremely unique, valuable and educational experience. I left the country knowing infinitely more about myself, the world, and what I am 'supposed' to do during my time in this world than I did before.
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: White, E. (2010). Human connection and social development : ?b lessons learned from a summer in Ghana. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Volunteer workers in child welfare--Ghana--Personal narratives; Student volunteers in social service--Ghana--Personal narratives; Disaster Volunteers of Ghana; Reports; Reports